The construction of a two-dimensional supramolecular organic framework with parallelogram pores and stepwise fluorescence enhancement. Issue 91 (28th September 2015) - Xu, Shun-Qi; Zhang, Xiang; Nie, Cheng-Bin; Pang, Zhong-Fu; Xu, Xiao-Na; Zhao, Xin
Abstract : A novel single-layer two-dimensional (2D) supramolecular organic framework (SOF) with parallelogram pores has been assembled and a stepwise fluorescence emission enhancement was observed. Abstract : A novel single-layer two-dimensional (2D) supramolecular organic framework (SOF) with parallelogram pores has been assembled to turn on the fluorescence emission of a non-emissive building block, and the emission could be further enhanced by the aggregation of the as-prepared 2D monolayers.